Method for producing anti-fogging laminate, anti-fogging laminate, and liquid composition

JP7643890B2Active Publication Date: 2025-03-11MITSUI CHEMICALS INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021032004
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-01
Publication Date
2025-03-11
Estimated Expiration
2041-03-01

AI Technical Summary

Benefits of technology

【0006】 本開示の一実施形態によれば、簡便な方法で防曇性積層体を製造できる防曇性積層体の製造方法、簡便な方法で製造できる防曇性積層体、及び、簡便な方法で防曇性積層体を製造できる液体組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643890000001
    Figure 0007643890000001
  • Figure 0007643890000002
    Figure 0007643890000002
  • Figure 0007643890000003
    Figure 0007643890000003
Patent Text Reader

Abstract

To provide a method for producing antifogging laminate in which an antifogging laminate can be produced by a simple method.SOLUTION: Provided is a method for producing antifogging laminate that comprises a preparation step of preparing a laminate that includes a substrate and a storage layer (A) and in which the storage layer (A) contains a resin (a1) that is at least one of an epoxy resin and an acrylic resin, an inorganic particle (a2), and a nonionic surfactant (a3), and an application step of applying an ionic surfactant-containing liquid composition on the surface of the laminate of the side in which the storage layer (A) is arranged.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing an anti-fog laminate, an anti-fog laminate, and a liquid composition. [Background technology]

[0002] In recent years, there has been an increasing demand for improvement in the fogging of substrates made of organic materials such as plastics and inorganic materials such as glass. As a method for solving the problem of fogging, for example, Patent Document 1 describes an anti-fogging article having a base and an anti-fogging film on at least a part of the surface of the base, the anti-fogging film having a base resin layer and a water-absorbent resin layer laminated in this order on the surface of the base, the water-absorbent resin layer being a water-absorbent resin layer mainly made of a first cured epoxy resin obtained by reacting a composition for forming a water-absorbent resin layer containing a specific polyepoxide component and a first curing agent, and the base resin layer being a base resin layer having a lower water absorbency than the water-absorbent resin layer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2012 / 077686 Summary of the Invention [Problem to be solved by the invention]

[0004] However, there is a demand for a method for producing an anti-fogging laminate that allows the anti-fogging laminate to be produced in a simpler manner. An object of the present invention is to provide an anti-fog laminate manufacturing method that can produce an anti-fog laminate by a simple method, an anti-fog laminate that can be produced by a simple method, and a liquid composition that can produce an anti-fog laminate by a simple method. [Means for solving the problem]

[0005] Specific means for solving the above problems include the following aspects. <1> a preparation step of preparing a laminate including a substrate and a storage layer (A), the storage layer (A) containing a resin (a1) which is at least one of an epoxy resin and an acrylic resin, inorganic particles (a2), and a nonionic surfactant (a3); a coating step of coating a liquid composition containing an ionic surfactant on the surface of the laminate on which the storage layer (A) is disposed; A method for producing an anti-fogging laminate comprising the steps of: <2> the laminate includes the base material, the storage layer (A), and a buffer layer (B) in contact with the storage layer (A) in this order; The buffer layer (B) contains a resin (b1) which is at least one of an epoxy resin and an acrylic resin, and inorganic particles (b2). <1> A method for producing the anti-fogging laminate according to claim 1. <3> The ionic surfactant includes at least one selected from the group consisting of fatty acid salts, alkyl ether carboxylates, alkanesulfonates, α-olefin sulfonates, α-sulfomethyl ester salts, alkylbenzenesulfonates, alkyl succinates, alkyl sulfates, and alkyl ether sulfates. <1> or <2> A method for producing the anti-fogging laminate according to claim 1. <4> The liquid composition does not contain an abrasive, or if it contains an abrasive, the content of the abrasive is 10 mass ppm or less based on the total amount of the liquid composition. <1> ~ <3> 13. A method for producing the anti-fogging laminate according to claim 12, <5> The nonionic surfactant (a3) ​​is a compound containing a polyoxyalkylene structure. <1> ~ <4> 13. A method for producing the anti-fogging laminate according to claim 12, <6> the preparing step includes preparing the laminate and releasing at least a portion of the nonionic surfactant (a3) ​​from the storage layer (A) in the prepared laminate, the coating step is a step of coating the liquid composition on a surface of the laminate on which the storage layer (A) is disposed, from which at least a portion of the nonionic surfactant (a3) ​​has been released; <1> ~ <5> 13. A method for producing the anti-fogging laminate according to claim 12, <7> A substrate and a reservoir layer (AX), The storage layer (AX) contains a resin (a1) which is at least one of an epoxy resin and an acrylic resin, inorganic particles (a2), a nonionic surfactant (a3), and an ionic surfactant. Anti-fog laminate. <8> A liquid composition is applied to a surface of a laminate on the side where the storage layer (A) is disposed, the laminate comprising a substrate and a storage layer (A), the storage layer (A) containing a resin (a1) which is at least one of an epoxy resin and an acrylic resin, inorganic particles (a2), and a nonionic surfactant (a3), A liquid composition comprising an ionic surfactant. Effect of the Invention

[0006] According to one embodiment of the present disclosure, it is possible to provide a manufacturing method for an anti-fog laminate that can produce an anti-fog laminate by a simple method, an anti-fog laminate that can be produced by a simple method, and a liquid composition that can produce an anti-fog laminate by a simple method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] In the present disclosure, a numerical range indicated using "~" means a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when there are multiple substances corresponding to each component, the amount of each component means the total amount of the multiple substances, unless otherwise specified. In the present disclosure, the term "step" refers not only to an independent step, but also to a step that cannot be clearly distinguished from other steps, as long as the purpose of the step is achieved.

[0008] [Method for producing anti-fogging laminate] The method for producing the anti-fogging laminate of the present disclosure includes the steps of: a preparation step of preparing a laminate including a substrate and a storage layer (A), the storage layer (A) containing a resin (a1) which is at least one of an epoxy resin and an acrylic resin, inorganic particles (a2), and a nonionic surfactant (a3); a coating step of coating a liquid composition containing an ionic surfactant on the surface of the laminate on which the storage layer (A) is disposed; Includes. The method for producing the anti-fogging laminate of the present disclosure may include other steps as necessary.

[0009] According to the method for producing an anti-fogging laminate of the present disclosure, the anti-fogging laminate can be produced by a simple method. The reason why such an effect is achieved is believed to be that by applying a liquid composition containing an ionic surfactant to the surface of the laminate on the side where the storage layer (A) is located, the ionic surfactant first penetrates into the interior of the storage layer (A), and then the penetrated ionic surfactant gradually migrates to the surface, thereby improving the anti-fogging properties of the surface (i.e., the ability to suppress fogging). Here, ionic surfactants are considered to be suitable as surfactants in the liquid composition to be applied in the above-mentioned application step, since they are more likely to penetrate into the interior of the storage layer (A) when applied to the storage layer (A) than nonionic surfactants.

[0010] Here, the surface of the laminate on the side where the storage layer (A) is disposed means the surface of the outermost layer on the side where the storage layer (A) is disposed of in the laminate. For example, the surface on which the storage layer (A) of the laminate is disposed is When the storage layer (A) is the outermost layer in the laminate, it means the surface of the storage layer (A), When another layer (such as the buffer layer (B) described below) is present on the storage layer (A) as the outermost layer in the laminate, the surface of the other layer (such as the buffer layer (B) described below) is meant.

[0011] The method for producing the anti-fogging laminate of the present disclosure is not particularly limited as long as it includes a preparation step and a coating step. For example, a method for producing the anti-fogging laminate of the present disclosure includes the steps of: It may be a method of imparting anti-fogging properties to a laminate that does not have anti-fogging properties by a coating process, The anti-fogging property of a laminate that originally has anti-fogging property may be further improved by a coating step. The method may be such that the anti-fogging property of a laminate, the anti-fogging property of which has been reduced, is restored by a coating step.

[0012] Hereinafter, each step of the method for producing the anti-fogging laminate of the present disclosure will be described.

[0013] <Preparation process> The preparation step is a step of preparing a laminate including a substrate and a storage layer (A), the storage layer (A) containing a resin (a1) which is at least one of an epoxy resin and an acrylic resin, inorganic particles (a2), and a nonionic surfactant (a3).

[0014] The preparation step may be a step of simply preparing the laminate that has been manufactured in advance, or may be a step of manufacturing the laminate.

[0015] In addition, the preparation process is Providing the laminate; Releasing at least a portion of the nonionic surfactant (a3) ​​from the storage layer (A) in the prepared laminate; may include: In this case, the antifogging properties of the laminate, which have been reduced due to the release of at least a portion of the nonionic surfactant (a3), can be restored by the coating step described below. There are no particular limitations on the method for releasing at least a portion of the nonionic surfactant (a3). The release of at least a portion of the nonionic surfactant (a3) ​​can be achieved, for example, by Simply aging the laminate; bringing water into contact with the surface of the laminate on which the storage layer (A) is disposed; This can be realized by gradually releasing the nonionic surfactant (a3) ​​from the reservoir layer (A) (hereinafter also referred to as sustained release) by the above-mentioned means.

[0016] (base material) The laminate prepared in the preparing step includes a substrate. The substrate is not particularly limited. Examples of the substrate include: Inorganic substrates made of inorganic materials such as glass, silica, metals, and metal oxides; Plastic substrates including poly(meth)acrylates such as polymethyl methacrylate (PMMA), polyurethanes, polythiourethanes, polycarbonates, polyallyl carbonates (e.g., allyl diglycol carbonate (ADC)), polyethylene terephthalate, polyacetyl cellulose (TAC), acrylonitrile-butadiene-styrene copolymers (ABS), polyethylene, polypropylene, polystyrene, epoxy resins, polyvinyl chloride resins, silicone resins, etc.; paper base material; Pulp base material; Organic-inorganic substrates such as SMC and BMC, which are composites of unsaturated polyester resin, fillers such as calcium carbonate, and glass fibers; etc. Further, a laminated substrate comprising the above-mentioned substrate and a layer of a cured coating material may also be used. Among the above, the substrate in the laminate is preferably a plastic substrate. The plastic substrate preferably contains at least one of polythiourethane, polycarbonate, and polyallyl carbonate, and more preferably contains at least one of polythiourethane and polycarbonate.

[0017] The shape of the substrate may be a plate shape, a film shape, a lens shape, or the like. The substrate is preferably a plastic substrate having a lens shape (that is, a plastic lens).

[0018] Furthermore, if necessary, the surface of the substrate may be subjected to a physical or chemical treatment, such as a corona treatment, an ozone treatment, a low-temperature plasma treatment using oxygen gas or nitrogen gas, a glow discharge treatment, an oxidation treatment using chemicals, or a flame treatment, for the purpose of activating the surface of the substrate. Instead of or in addition to these treatments, a primer treatment, an undercoat treatment, an anchor coat treatment, etc. may be performed.

[0019] Examples of the coating agent used in the primer treatment, undercoat treatment, and anchor coat treatment include coating agents that contain a resin such as a polyester resin, a polyamide resin, a polyurethane resin, an epoxy resin, a phenol resin, a (meth)acrylic resin, a polyvinyl acetate resin, a polyolefin resin such as polyethylene and polypropylene, or a copolymer or modified resin thereof, or a cellulose resin as a main component of the vehicle. The coating agent used here may be a conventionally known one that is usually used in the field to which the present disclosure belongs, and the coating agent can be applied by a known painting method. The amount of the coating agent applied to the substrate is preferably 0.5 μm to 10 μm in a dry state.

[0020] (Storage layer (A)) The laminate prepared in the preparation step includes a storage layer (A). The storage layer (A) contains a resin (a1) which is at least one of an epoxy resin and an acrylic resin, inorganic particles (a2), and a nonionic surfactant (a3).

[0021] -Resin (a1)- The resin (a1) contained in the storage layer (A) may be at least one of an epoxy resin and an acrylic resin. The resin (a1) contained in the storage layer (A) may be of one type or of two or more types.

[0022] The content of the resin (a1) relative to the total mass of the storage layer (A) is preferably 30% by mass to 70% by mass, and more preferably 40% by mass to 60% by mass. Here, the content of resin (a1) relative to the total mass of the storage layer (A) essentially corresponds to the content of monomer for forming resin (a1) (hereinafter also referred to as "monomer for forming resin (a1)") relative to the total solid content (i.e., the total amount excluding the solvent) of the composition for forming the storage layer (A) (hereinafter also referred to as "composition for forming storage layer (A)"). Examples of the monomer for forming the resin (a1) include the polyfunctional epoxy monomer described below and the polyfunctional (meth)acrylic monomer described below.

[0023] -Epoxy resin- The epoxy resin that can be contained in the resin (a1) is preferably formed using a monomer containing two or more epoxy groups (hereinafter, also referred to as a polyfunctional epoxy monomer). The polyfunctional epoxy monomer is polymerized to form a network structure that serves as the basic skeleton of the reservoir layer (A). In the reservoir layer (A), spaces are formed as gaps in the network structure to store the surfactant (i.e., the nonionic surfactant (a3) ​​and / or the ionic surfactant applied in the coating step).

[0024] The molecular weight of the polyfunctional epoxy monomer is preferably 100-2,000, and more preferably 150-1,500.

[0025] The polyfunctional epoxy monomer preferably contains a polyfunctional epoxy monomer (AE1) having a molecular weight per epoxy group in one molecule (hereinafter also referred to as epoxy equivalent) of 200 g / mol or more. By including the multifunctional epoxy monomer (AE1), the molecular weight required for forming the layer can be ensured while the number of reaction sites for the crosslinking reaction can be reduced, which allows the storage layer (A) to easily retain moisture, thereby further improving the anti-fogging properties of the laminate. The epoxy equivalent of the polyfunctional epoxy monomer (AE1) is preferably 300 g / mol or more, and more preferably 350 g / mol or more.

[0026] On the other hand, the polyfunctional epoxy monomer (AE1) preferably has an epoxy equivalent of 500 g / mol or less. By making the epoxy equivalent of the polyfunctional epoxy monomer (AE1) 500 g / mol or less, the crosslinking reaction can be more effectively promoted, so that a laminate having better scratch resistance can be obtained. The epoxy equivalent of the polyfunctional epoxy monomer (AE1) is more preferably 450 g / mol or less.

[0027] The multifunctional epoxy monomer (AE1) is preferably a difunctional epoxy monomer.

[0028] Multifunctional epoxy monomer (AE1) It may contain an alkane polyol structure such as an alkane diol or an alkane triol, The polyoxyalkylene may contain an oxyalkylene structure, such as polyoxyalkylene glycol (eg, polyethylene glycol) or a compound obtained by adding polyoxyalkylene to an alkane polyol.

[0029] Among the above, from the viewpoint of improving water absorption and obtaining better anti-fogging properties, it is preferable that the polyfunctional epoxy monomer (AE1) contains an oxyalkylene structure.

[0030] The oxyalkylene structure may have a hydrophilic group as a substituent. When the oxyalkylene structure has a hydrophilic group, the water absorbency of the laminate can be improved. Examples of the hydrophilic group include a hydroxyl group, a carboxyl group, and a sulfonic acid group. Among the above, the hydrophilic group is preferably a hydroxyl group, and more preferably a diol. An example of the polyfunctional epoxy monomer (AE1) is a diol containing a polyoxyethylene structure.

[0031] The polyfunctional epoxy monomer (AE1) may further contain an aromatic ring, or may be an alicyclic compound. Examples of the polyfunctional epoxy monomer (AE1) containing an aromatic ring include ethylene oxide adducts of bisphenols. The linker portion (ie, the portion other than the epoxy group) in the polyfunctional epoxy monomer (AE1) preferably has a chain structure from the viewpoint of improving antifogging properties.

[0032] The molecular weight of the polyfunctional epoxy monomer (AE1) is preferably 300-2,000, and more preferably 300-1,000.

[0033] As the polyfunctional epoxy monomer (AE1), a commercially available product may be used. An example of a commercially available product is Denacol EX-841 (manufactured by Nagase ChemteX Corporation).

[0034] The polyfunctional epoxy monomer may contain, in addition to the above-mentioned polyfunctional epoxy monomer (AE1), a polyfunctional epoxy monomer (AE2) having an epoxy equivalent of less than 200 g / mol. This can increase the number of reaction points for the crosslinking reaction, thereby improving the degree of crosslinking, and as a result, the scratch resistance of the laminate can be further improved.

[0035] The polyfunctional epoxy monomer (AE2) preferably contains a compound represented by the following formula (AE2-1).

[0036] [ka]

[0037] In formula (AE2-1), X is an alkylene group having 2 to 6 carbon atoms, and n is an integer of 1 to 5. In formula (AE2-1), when n is an integer of 2 to 5, multiple Xs may be the same or different.

[0038] In formula (AE2-1), the alkylene group having 2 to 6 carbon atoms for X is preferably an alkylene group having 2 or 3 carbon atoms. The alkylene group having 2 to 6 carbon atoms may or may not have a substituent. Examples of the substituent include a hydrophilic group (such as a hydroxyl group or a carboxyl group), a glycidyl ether group, and an alkyl group having a hydrophilic group or a glycidyl ether group.

[0039] The molecular weight of the polyfunctional epoxy monomer (AE2) is preferably 100-2,000, and more preferably 150-1,500.

[0040] As the polyfunctional epoxy monomer (AE2), a commercially available product may be used. Commercially available products include Denacol EX-313 and Denacol EX-521 (both manufactured by Nagase ChemteX Corporation).

[0041] The polyfunctional epoxy monomer used to form the epoxy resin in the resin (a1) may be one type or two or more types.

[0042] When forming a storage layer (A) containing an epoxy resin as the resin (a1), the content of the polyfunctional epoxy monomer relative to the total amount of all monomers contained in the composition for forming the storage layer (A) is preferably 70 mass% or more, and more preferably 75 mass% or more.

[0043] When forming a storage layer (A) containing an epoxy resin as the resin (a1), the total content of the polyfunctional epoxy monomer is preferably 30% by mass to 70% by mass, and more preferably 40% by mass to 60% by mass, based on the total solid content of the composition for forming the storage layer (A) (i.e., the total amount excluding the solvent).

[0044] When the composition for forming the storage layer (A) contains a polyfunctional epoxy monomer (AE1) and a polyfunctional epoxy monomer (AE2), the ratio of the polyfunctional epoxy monomer (AE1) to the total mass of the polyfunctional epoxy monomer (AE1) and the polyfunctional epoxy monomer (AE2) is preferably 5 mass% to 50 mass%, and more preferably 10 mass% to 40 mass%.

[0045] The composition for forming the storage layer (A) may further contain a polyfunctional monomer containing an oxetane ring. The polyfunctional monomer containing an oxetane ring preferably contains two oxetane rings. Moreover, the polyfunctional monomer containing an oxetane ring preferably contains an ether bond (excluding the ether bond of the oxetane ring). Examples of polyfunctional monomers containing an oxetane ring include Aron Oxetane OXT-221 (Toagosei Co., Ltd.).

[0046] -Acrylic resin- The acrylic resin that can be contained in the resin (a1) is preferably formed using a monomer containing two or more (meth)acryloyl groups (hereinafter, also referred to as a polyfunctional (meth)acrylic monomer). The polyfunctional (meth)acrylic monomer is polymerized to form a network structure that serves as the basic skeleton of the reservoir layer (A). In the reservoir layer (A), spaces are formed as gaps in the network structure to store the surfactant (i.e., the nonionic surfactant (a3) ​​and / or the ionic surfactant applied in the coating step).

[0047] In the present disclosure, a (meth)acryloyl group means an acryloyl group or a methacryloyl group, and a (meth)acrylic monomer means an acrylic monomer or a methacrylic monomer. Further, the concept of acrylic resin in this disclosure encompasses not only resins formed by polymerization of acrylic monomers, but also resins formed by polymerization of methacrylic monomers.

[0048] The polyfunctional (meth)acrylic monomer preferably comprises two or more (meth)acryloyl groups and a linker moiety that fixes these two or more (meth)acryloyl groups within one molecule. The polyfunctional (meth)acrylic monomer is preferably an ester of (meth)acrylic acid and a polyhydric alcohol having two or more hydroxyl groups. Here, examples of the "polyhydric alcohol having two or more hydroxyl groups" include: Alkane polyols such as alkane diols and alkane triols; Compounds containing a polyoxyalkylene structure, such as polyalkylene glycols (e.g., polyethylene glycol, polypropylene glycol, etc.) and compounds obtained by adding polyalkylene glycol to alkane polyol; etc. The "polyhydric alcohol having two or more hydroxyl groups" may contain an aromatic ring and / or an aliphatic ring. Examples of the "polyhydric alcohol having two or more hydroxyl groups" containing an aromatic ring include ethylene oxide adducts of bisphenols.

[0049] As the "polyhydric alcohol having two or more hydroxyl groups", a compound containing a polyoxyalkylene structure is preferable, and a diol containing a polyoxyethylene structure is more preferable.

[0050] Specific examples of the polyfunctional (meth)acrylic monomer include compounds represented by the following formula (AA1) or (AA2). The polyfunctional (meth)acrylic monomer preferably contains a compound represented by the following formula (AA1).

[0051] [ka]

[0052] In formula (AA1), n ​​represents an integer of 1 to 30. In formula (AA2), l and m are numbers such that l+m is an integer of 2 to 40.

[0053] Specific examples of polyfunctional (meth)acrylic monomers include polyethylene glycol diacrylate and 2,2-bis-[4-(acryloxy-polyethoxy)phenyl]-propane. Examples of the polyethylene glycol di(meth)acrylate include tetradecaethylene glycol di(meth)acrylate and tricosaethylene glycol di(meth)acrylate.

[0054] The polyfunctional (meth)acrylic monomer used to form the acrylic resin in the resin (a1) may be one type or two or more types.

[0055] When forming a storage layer (A) containing an acrylic resin as the resin (a1), the content of the polyfunctional (meth)acrylic monomer relative to the total amount of all monomers contained in the composition for forming the storage layer (A) is preferably 70 mass% or more, and more preferably 75 mass% or more.

[0056] When forming a storage layer (A) containing an acrylic resin as the resin (a1), the total content of the polyfunctional (meth)acrylic monomer is preferably 30% by mass to 70% by mass, and more preferably 40% by mass to 60% by mass, based on the total solid content of the composition for forming the storage layer (A) (i.e., the total amount excluding the solvent).

[0057] -Inorganic particles (a2)- The storage layer (A) contains at least one type of inorganic particles (a2). This provides the storage layer (A) with excellent hardness and strength. The inorganic particles (a2) may be present inside the storage layer (A) preferably in a form incorporated into a network structure in the resin (a1).

[0058] The inorganic particles (a2) are The inorganic particles (a2-0) may be inorganic particles (a2-0) that are not modified with a functional group (hereinafter, simply referred to as "inorganic particles (a2-0)"). They may also be inorganic particles (a2-1) modified with a functional group (hereinafter simply referred to as "inorganic particles (a2-1)").

[0059] The inorganic particles (a2-0) are unmodified inorganic particles, that is, the inorganic particles (a2-0) are particles consisting essentially of inorganic substances. The above "particles consisting essentially of inorganic substances" does not mean that the content of organic substances in the inorganic particles (a2-0) is strictly 0. In other words, the inorganic particles (a2-0) may contain a trace amount of organic substances that do not show reactivity with other components, to the extent that the organic substances do not affect the inherent physical properties of the inorganic substances that constitute the inorganic particles (a2-0). For example, the inorganic particles (a2-0) may contain a trace amount of organic matter that may be inevitably mixed in during the production process, or a trace amount of organic matter derived from the atmosphere that may be inevitably nonspecifically adsorbed to the surface when left in the atmosphere.

[0060] Examples of inorganic substances constituting the inorganic particles (a2-0) include silica, zirconia, alumina, tin oxide, antimony oxide, metal oxides such as titania, nanodiamond particles, and the like. Among the above, silica and zirconia are preferred as the inorganic substance constituting the inorganic particles (a2-0) from the viewpoints of dispersibility in the resin (a1), hardness of the laminate, and light resistance.

[0061] The particle size of the inorganic particles (a2-0) is preferably from 5 nm to 50 nm. When the particle diameter of the inorganic particles (a2-0) is 5 nm or more, the hardness of the laminate can be improved, and the dispersibility is also superior. On the other hand, when the particle size of the inorganic particles (a2-0) is 50 nm or less, the transparency of the storage layer (A) can be improved. The particle size of the inorganic particles (a2-0) is more preferably from 10 nm to 30 nm.

[0062] The particle size of the inorganic particles (a2-0) is measured by a dynamic scattering method using laser light. The inorganic particles (a2-0) may be of one type alone or a combination of two or more types.

[0063] The inorganic particles (a2-0) are commercially available, for example, PGM-ST manufactured by Nissan Chemical Industries, Ltd.

[0064] The inorganic particles (a2) may be inorganic particles (a2-1) modified with a functional group. The inorganic particles (a2-1) are particles in which the above-mentioned inorganic particles (a2-0) are used as base particles, and the surfaces of the above-mentioned base particles are modified with functional groups. The functional group preferably contains at least one of an epoxy group and a (meth)acryloyl group.

[0065] The inorganic particles (a2-1) are commercially available, and examples thereof include PGM-AC-2140Y and MEK-EC-2430Z (both manufactured by Nissan Chemical Industries, Ltd.).

[0066] The content of the inorganic particles (a2) relative to the total mass of the storage layer (A) is preferably 30% by mass or more, which further improves the scratch resistance of the resulting laminate. From the same viewpoint as above, the content of the inorganic particles (a2) relative to the total mass of the storage layer (A) is preferably 40 mass % or more, and more preferably 50 mass % or more. There is no particular upper limit to the content of the inorganic particles (a2) relative to the total mass of the storage layer (A). The content of the inorganic particles (a2) relative to the total mass of the storage layer (A) may be, for example, 70 mass% or less, or 60 mass% or less.

[0067] Here, the content of the inorganic particles (a2) relative to the total mass of the storage layer (A) substantially corresponds to the content of the inorganic particles (a2) relative to the total solid content of the composition for forming the storage layer (A). The same applies to each component in the storage layer (A) and each component in the buffer layer (B) hereinafter.

[0068] In the composition for forming the storage layer (A), the ratio of the inorganic particles (a2) to the monomer for forming the resin (a1) is preferably 0.6 to 1.8, and more preferably 0.8 to 1.6. In the storage layer (A), the ratio of the inorganic particles (a2) to the resin (a1) is preferably 0.6 to 1.8, and more preferably 0.8 to 1.6.

[0069] -Nonionic surfactant (a3)- The storage layer (A) contains at least one nonionic surfactant (a3). The nonionic surfactant (a3) ​​is a component that is slowly released (i.e., gradually released) from the storage layer (A) and migrates to the surface of the laminate on which the storage layer (A) is located, thereby exerting the anti-fogging properties of the laminate. In the manufacturing method of the anti-fogging laminate of the present disclosure, the effect of the nonionic surfactant (a3) ​​originally contained in the storage layer (A) and the effect of the ionic surfactant imparted to the storage layer (A) in the coating step are combined to produce an anti-fogging laminate with superior anti-fogging properties.

[0070] The nonionic surfactant (a3) ​​has an advantage over the ionic surfactant in that it has a smaller effect on the polymerization of the monomer for forming the resin (a1) when the storage layer (A) is formed.

[0071] As described above, the nonionic surfactant (a3) ​​in the storage layer (A) can be released from the storage layer (A). Therefore, at the time of the coating step, the content of the nonionic surfactant (a3) ​​relative to the total mass of the storage layer (A) may be reduced compared to that immediately after the formation of the storage layer (A). Even in this case, the antifogging properties of the laminate can be restored by adding an ionic surfactant in the coating step.

[0072] In the laminate, the content of the nonionic surfactant (a3) ​​relative to the total mass of the storage layer (A) is not particularly limited. The content of the nonionic surfactant (a3) ​​relative to the total mass of the storage layer (A) may be, for example, more than 0 mass% and not more than 10 mass%, more than 0 mass% and not more than 5 mass%, more than 0 mass% and not more than 3 mass%, or more than 0 mass% and not more than 1 mass%. The lower limit of the content of the nonionic surfactant (a3) ​​relative to the total mass of the storage layer (A) may be, for example, 0.1 mass % or 0.3 mass %.

[0073] As described above, the preparation step may also include preparing a laminate and releasing at least a portion of the nonionic surfactant (a3) ​​from the storage layer (A) in the prepared laminate (e.g., by allowing the laminate to age). In this case, the content of the nonionic surfactant (a3) ​​relative to the total mass of the storage layer (A) at the stage at which at least a portion of the nonionic surfactant (a3) ​​has been released (i.e., at the stage at which the storage layer (A) is subjected to the coating process) may be more than 0 mass% and not more than 1 mass%, or may be more than 0 mass% and not more than 0.5 mass%. In the above case, the content of the nonionic surfactant (a3) ​​relative to the total mass of the storage layer (A) before at least a portion of the nonionic surfactant (a3) ​​is released may be 0.1% by mass to 10% by mass, 0.3% by mass to 10% by mass, or 1% by mass to 5% by mass.

[0074] As the nonionic surfactant (a3), Preferably, it is a compound containing a polyoxyalkylene structure, More preferred are compounds containing a hydrocarbon group and a polyoxyalkylene structure. Examples of the hydrocarbon group include an alkyl group and an alkenyl group.

[0075] Examples of the compound containing a hydrocarbon group and a polyoxyalkylene structure as the nonionic surfactant (a3) ​​include: polyoxyalkylene alkyl ethers such as polyoxyalkylene monoalkyl ethers; polyoxyalkylene alkenyl ethers, such as polyoxyalkylene monoalkenyl ethers; A mixture of these; etc. Examples of the polyoxyalkylene alkyl ether include polyoxyethylene alkyl ethers (for example, polyoxyethylene isodecyl ether, polyoxyethylene lauryl ether, etc.).

[0076] The compound containing a hydrocarbon group and a polyoxyalkylene structure as the nonionic surfactant (a3) ​​may further contain an anionic hydrophilic group. Examples of the nonionic surfactant (a3) ​​containing an anionic hydrophilic group include polyoxyalkylene alkyl ether sulfates, polyoxyalkylene alkenyl ether sulfates, and mixtures thereof.

[0077] As the nonionic surfactant (a3), a commercially available product may be used. An example of a commercially available product is Noigen LP-100 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., polyoxyalkylene lauryl ether).

[0078] -Other ingredients- The storage layer (A) may contain other components in addition to the above components. As for other components, reference can be made to the components of the composition for forming the storage layer (A) described below.

[0079] (Composition for forming storage layer (A) and method for forming storage layer (A)) The composition for forming the storage layer (A) can contain the above-mentioned monomer for forming the resin (a1) (e.g., a polyfunctional epoxy monomer, a polyfunctional (meth)acrylic monomer, etc.), the above-mentioned inorganic particles (a2), and the above-mentioned nonionic surfactant (a3).

[0080] The storage layer (A) in the laminate can be formed by applying a composition for forming a storage layer (A) onto a substrate and curing the applied composition for forming a storage layer (A). The composition for forming the storage layer (A) can be applied to the substrate by a conventional method, such as spin coating, dip coating, spray coating, flow coating, brush coating, gravure coating, reverse roll coating, knife coating, kiss coating, etc. Prior to application of the composition for forming the storage layer (A), other layers (e.g., a primer layer, a hard coat layer, etc.) may be formed on the substrate. In this case, the composition for forming the storage layer (A) is applied to the region of the substrate where the other layers are formed. In addition, the surface of the substrate on which the composition for forming the storage layer (A) is applied (or on which other layers are formed, if other layers are to be formed) may be previously subjected to a surface treatment such as plasma treatment, corona treatment, polishing treatment, etc.

[0081] The composition for forming the storage layer (A) applied onto the substrate is cured by polymerizing the monomer for forming the resin (a1) described above. When the resin (a1)-forming monomer contains a polyfunctional epoxy monomer (ie, when the resin (a1) contains an epoxy resin), the polymerization of the resin (a1)-forming monomer is preferably carried out at least by thermal polymerization. When the resin (a1)-forming monomer contains a polyfunctional (meth)acrylic monomer (ie, when the resin (a1) contains an acrylic resin), the polymerization of the resin (a1)-forming monomer is preferably carried out at least by photopolymerization.

[0082] In the present disclosure, the term "light" in "photopolymerization" and the like means active energy rays such as ultraviolet light and visible light.

[0083] The thermal polymerization is carried out, for example, by heating the composition for forming the storage layer (A) applied onto the substrate, for example, within the range of room temperature to 150° C. In this case, the heating time can be appropriately set. The photopolymerization is carried out, for example, by irradiating the storage layer (A) forming composition applied onto the substrate with active energy rays. As the active energy rays, active energy rays having a wavelength region ranging from 0.0001 nm to 800 nm can be used. Examples of the active energy rays include α rays, β rays, γ rays, X-rays, electron beams, ultraviolet rays (UV), and visible light.

[0084] -Polymerization initiator- The composition for forming the storage layer (A) preferably contains at least one type of polymerization initiator. The polymerization initiator is preferably at least one of a thermal polymerization initiator and a photopolymerization initiator. When the resin (a1)-forming monomer contains a polyfunctional epoxy monomer (that is, when the resin (a1) contains an epoxy resin), the polymerization initiator preferably contains at least a thermal polymerization initiator. When the resin (a1)-forming monomer contains a polyfunctional (meth)acrylic monomer (that is, when the resin (a1) contains an acrylic resin), the polymerization initiator preferably contains at least a photopolymerization initiator.

[0085] As the thermal polymerization initiator, known thermal polymerization initiators can be used. For example, ketone peroxides, diacyl peroxides, dialkyl peroxides, peroxyketals, alkyl peresters, percarbonates, aluminum chelating agents, thermal acid generators, etc. may be mentioned. Among the above, as the thermal polymerization initiator, an aluminum chelating agent and a thermal acid generator are preferred from the viewpoint of improving scratch resistance. An example of an aluminum chelating agent is Aluminum Chelate A(W) (manufactured by Kawaken Fine Chemicals Co., Ltd.). An example of the thermal acid generator is San-Aid SI-60L (manufactured by Sanshin Chemical Industry Co., Ltd.).

[0086] Examples of the photopolymerization initiator include a photoradical polymerization initiator, a photocationic polymerization initiator, and a photoanionic polymerization initiator. An example of the photoradical polymerization initiator is Omnirad184 (manufactured by IGM Resins BV). An example of the photocationic polymerization initiator is San-Apro CP-210S (Sanyo Chemical Industries, Ltd.).

[0087] The content of the polymerization initiator relative to the total solid content of the composition for forming the storage layer (A) is preferably 0.1 to 10% by mass, and more preferably 0.5 to 5% by mass. The preferable range of the content of the polymerization initiator relative to the total mass of the storage layer (A) to be formed is also the same.

[0088] -solvent- The composition for forming the storage layer (A) may contain at least one solvent. The solvent is not particularly limited, but may be, for example: Alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, t-butanol, n-pentanol, isopentanol, n-hexanol, n-octanol, 2-ethyl-hexanol, 2-methoxyethanol, 2-ethoxyethanol, 2-n-propoxyethanol, 2-isopropoxyethanol, 2-butoxyethanol, 1-methoxy-2-propanol (also known as propylene glycol monomethyl ether), 1-ethoxy-2-propanol (also known as propylene glycol monoethyl ether), 1-n-propoxy-2-propanol, 1-isopropoxy-2-propanol, and cyclohexanol; Ethers such as diethyl ether, tetrahydrofuran, and dioxane; Nitriles such as acetonitrile; Esters such as ethyl acetate, n-propyl acetate, and n-butyl acetate; Ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; amides such as N,N-dimethylformamide and N,N-dimethylacetamide; water; etc. The solvent is preferably an alcohol, a ketone, or a mixture thereof.

[0089] (Buffer layer (B)) The laminate prepared in the preparing step may include the above-mentioned base material, the above-mentioned storage layer (A), and a buffer layer (B) in contact with the above-mentioned storage layer (A) in this order. Here, the buffer layer (B) contains a resin (b1) which is at least one of an epoxy resin and an acrylic resin, and inorganic particles (b2).

[0090] The components contained in the buffer layer (B) are similar to the components contained in the storage layer (A) except that they are not limited to containing a nonionic surfactant, and the preferred aspects (e.g., type, content, etc.) are also similar. For example, preferred embodiments of the resin (b1) and inorganic particles (b2) contained in the buffer layer (B) are the same as the preferred embodiments of the resin (a1) and inorganic particles (a2) contained in the storage layer (A), respectively.

[0091] The buffer layer (B) may contain a nonionic surfactant (b3). In this case, the preferred embodiments of the nonionic surfactant (b3) contained in the buffer layer (B) are the same as the preferred embodiments of the nonionic surfactant (a3) ​​contained in the storage layer (A). It is preferable that the buffer layer (B) does not contain a nonionic surfactant (b3), or, even if it contains a nonionic surfactant (b3), the ratio of the content of the nonionic surfactant (b3) to the total mass of the buffer layer (B) is smaller than the ratio of the content of the nonionic surfactant (a3) ​​to the total mass of the storage layer (A) (in particular, the ratio of the content of the nonionic surfactant (a3) ​​to the total mass of the storage layer (A) at the stage before the content of the nonionic surfactant (a3) ​​described above is reduced). This further promotes the migration of the nonionic surfactant (a3) ​​from the storage layer (A) to the buffer layer (B), thereby further improving the antifogging properties of the laminate. From the above viewpoints, the ratio [the ratio of the content of the nonionic surfactant (b3) to the total mass of the buffer layer (B) / the ratio of the content of the nonionic surfactant (a3) ​​to the total mass of the storage layer (A)] is preferably 0 / 10 to 8 / 10, more preferably 0 / 10 to 5 / 10, and even more preferably 0 / 10 to 3 / 10.

[0092] Moreover, the ratio of the thickness of the storage layer (A) to the thickness of the buffer layer (B) is preferably 1.3 or more, more preferably 1.5 or more, and even more preferably 1.7 or more. The upper limit of the above ratio is preferably 15 or less, more preferably 5 or less, and even more preferably 3.5 or less.

[0093] (Other layers) The laminate may further include other layers in addition to the substrate, the storage layer (A), and the buffer layer (B). Examples of the other layers include a primer layer, a hard coat layer, and an adhesive layer.

[0094] <Coating process> The coating step is a step of coating a liquid composition containing an ionic surfactant onto the surface of the laminate prepared in the preparation step on the side where the storage layer (A) is disposed. By this coating step, the ionic surfactant permeates from the surface of the laminate and reaches the storage layer (A). The ionic surfactant that reaches the storage layer (A) is gradually released over time together with the nonionic surfactant originally contained therein, thereby exerting excellent anti-fogging properties on the surface of the laminate. That is, an anti-fogging laminate having excellent anti-fogging properties can be obtained by the coating step.

[0095] The method for applying the liquid composition is not particularly limited, and for example, the examples of the application method for applying the composition for forming the storage layer (A) to the base material can be appropriately referred to.

[0096] In the coating step, after coating of the liquid composition, the liquid composition may be left without being wiped off in order to allow the ionic surfactant to penetrate into the storage layer (A). The time for leaving the liquid composition is, for example, 30 seconds or more, more preferably 1 minute or more, even more preferably 5 minutes or more, and even more preferably 10 minutes or more.

[0097] -Liquid composition- The liquid composition contains at least one ionic surfactant. The ionic surfactant may be an anionic surfactant or a cationic surfactant, but preferably includes an anionic surfactant. For specific examples of ionic surfactants (particularly, anionic surfactants), see, for example, paragraph 0018 of WO 2016 / 111035.

[0098] The ionic surfactant preferably contains at least one selected from the group consisting of fatty acid salts, alkyl ether carboxylates, alkanesulfonates, α-olefin sulfonates, α-sulfomethyl ester salts, alkylbenzenesulfonates, alkyl succinates, alkyl sulfates, and alkyl ether sulfates.

[0099] Examples of alkyl ether sulfates include sodium 2-ethylhexyl sulfate, sodium lauryl sulfate, sodium alkyl sulfate, sodium polyoxyethylene lauryl ether sulfate, and sodium polyoxyethylene alkyl ether sulfate (AES). An example of the alkylbenzene sulfonate is sodium linear alkylbenzene sulfonate (LAS).

[0100] The content of the ionic surfactant relative to the total amount of the liquid composition is preferably 1% by mass to 40% by mass, more preferably 5% by mass to 35% by mass, and even more preferably 10% by mass to 30% by mass.

[0101] The liquid composition preferably contains water as a solvent. The content of water relative to the total amount of the liquid composition is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more.

[0102] The liquid composition may contain other components in addition to the above components.

[0103] From the viewpoint of further suppressing scratches on the surface of the laminate, it is preferable that the liquid composition does not contain an abrasive (e.g., inorganic filler such as alumina or silica), or, if it contains an abrasive, the content of the abrasive is 10 ppm by mass or less relative to the total amount of the liquid composition.

[0104] [Anti-fogging laminate] The anti-fogging laminate of the present disclosure comprises: A substrate and a reservoir layer (AX), The storage layer (AX) contains a resin (a1) which is at least one of an epoxy resin and an acrylic resin, inorganic particles (a2), a nonionic surfactant (a3), and an ionic surfactant.

[0105] The antifogging laminate of the present disclosure includes a storage layer (AX) containing a nonionic surfactant (a3) ​​and an ionic surfactant, which provides an effect of gradually releasing the nonionic surfactant (a3) ​​and the ionic surfactant from the storage layer (AX), thereby providing excellent antifogging properties.

[0106] The substrate in the anti-fogging laminate of the present disclosure is the same as the substrate in the laminate prepared in the above-mentioned preparation step. The storage layer (AX) in the anti-fog laminate of the present disclosure is similar to the storage layer (A) in the laminate prepared in the preparation step described above, except that an ionic surfactant is added as an essential component. The anti-fogging laminate of the present disclosure may have the same characteristics as the laminate prepared in the preparation step described above, such as the buffer layer (B).

[0107] The anti-fog laminate of the present disclosure is preferably produced by the above-mentioned method for producing the anti-fog laminate of the present disclosure. In this case, an ionic surfactant is applied to the storage layer (A) in the laminate prepared in the preparation step in the coating step. This converts the storage layer (A) into the storage layer (AX). That is, in this case, the layer to which the ionic surfactant is applied to the storage layer (A) is the storage layer (AX).

[0108] [Liquid composition] The liquid composition of the present disclosure comprises: A liquid composition is applied to a surface of a laminate on the side where the storage layer (A) is disposed, the laminate comprising a substrate and a storage layer (A), the storage layer (A) containing a resin (a1) which is at least one of an epoxy resin and an acrylic resin, inorganic particles (a2), and a nonionic surfactant (a3), Contains an ionic surfactant.

[0109] By applying the liquid composition of the present disclosure to the surface of the laminate on which the storage layer (A) is disposed, the antifogging properties of the above surface of the laminate are improved, as described above. The liquid composition of the present disclosure is similar to the liquid composition used in the above-mentioned coating step, and preferred aspects are also similar. EXAMPLES

[0110] Examples of the present disclosure will be described below, but the present disclosure is not limited to the following examples.

[0111] [Preparation of Compositions A1 to A6 for Forming Storage Layer (A) and Compositions B2 and B3 for Forming Buffer Layer (B)] Compositions A1 to A6 for forming the storage layer (A), and compositions B2 and B3 for forming the buffer layer (B), each containing the components shown in Tables 1 and 2 below and propylene glycol monomethyl ether as a dilution solvent, were prepared.

[0112] [Table 1]

[0113] [Table 2]

[0114] In Tables 1 and 2, "-" means that the corresponding component is not contained. In Tables 1 and 2, the amount of inorganic particles indicates the amount of components other than the solvent (ie, solid content) in the sol of inorganic particles (ie, silica sol).

[0115] The components in Tables 1 and 2 are as follows. Denacol EX-841 (Nagase Chemtex Corporation. A multifunctional monomer for forming epoxy resins. More specifically, polyethylene glycol diglycidyl ether. Epoxy equivalent: 372.) Denacol EX-521 (Nagase Chemtex Corporation. A multifunctional monomer for forming epoxy resins. Specifically, polyglycerol polyglycidyl ether. Epoxy equivalent: 183.) Denacol EX-313 (Nagase Chemtex Corporation. A multifunctional monomer for forming epoxy resins. Specifically, glycerol polyglycidyl ether. Epoxy equivalent: 141.) NK Ester A-1000 (manufactured by Shin-Nakamura Chemical Co., Ltd. A multifunctional monomer for forming acrylic resin. Specifically, polyethylene glycol diacrylate) NK Ester A-BPE-30 (manufactured by Shin-Nakamura Chemical Co., Ltd. A multifunctional monomer for forming acrylic resins. Specifically, ethoxylated bisphenol A diacrylate) Epoxy Ester 80MFA (manufactured by Kyoeisha Chemical Co., Ltd. A multifunctional monomer for forming acrylic resin. Specifically, Epolite 80MF acrylic acid adduct)

[0116] Unmodified silica sol (Nissan Chemicals, PGM-ST, solid content 30% by mass) Acrylic modified silica sol (Nissan Chemical, PGM-AC-2140Y, solid content 30% by mass) Epoxy-modified silica sol (Nissan Chemical, MEK-EC-2430Z, solid content 30% by mass)

[0117] San-Aid SI-60L (manufactured by Sanshin Chemical Industry Co., Ltd., cationic polymerization initiator, solid content 32% by mass) Omnirad 184 (manufactured by IGM Resins BV. Radical polymerization initiator. Specifically, 1-hydroxycyclohexyl-phenyl ketone)

[0118] Noigen LP-100 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd. A nonionic surfactant. Specifically, polyoxyalkylene lauryl ether)

[0119] Example 1 <Production of Laminate> A composition A1, which is a composition for forming a storage layer (A), was applied by dip coating onto a lens substrate (RAV 7AX, manufactured by Shanghai Conant Optics, a plano lens with a diameter of 70 mm, made of allyl diglycol carbonate (ADC); hereinafter also referred to as "ADC lens") as a substrate, to obtain a coating film. The dip coating was performed by using composition A1 in a PP beaker as a coating liquid, immersing the ADC lens in the coating liquid for 10 seconds, and then pulling it up at a speed of 350 mm per minute. The coating film formed on the substrate was heated and cured at 110° C. for 60 minutes to form a storage layer A1 as the storage layer (A). In this manner, a laminate including a substrate (an ADC lens in this Example 1) and a storage layer (A) (a storage layer A1 in this Example 1) was obtained.

[0120] <Application of liquid composition containing ionic surfactant> On the surface of the storage layer (A) of the laminate, 2 g of a 25% by mass aqueous solution of polyoxyethylene alkyl ether sulfate sodium (AES) (specifically, "Hitenol 325SM" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as a liquid composition containing an ionic surfactant was attached and uniformly applied. Then, the laminate was left in a temperature environment of 22°C for 20 minutes, and the liquid composition was thoroughly absorbed into the surface of the storage layer (A). Next, the liquid composition on the surface of the storage layer (A) was washed off with tap water for 10 seconds, and the liquid composition remaining on the surface was blown off with an air blower and then wiped off with tissue paper.

[0121] <Evaluation> The laminate after wiping off the liquid composition was used to carry out the following evaluations. The results are shown in Table 3.

[0122] (contact angle) The contact angle of pure water on the surface of the storage layer (A) in the laminate was measured using a contact angle meter (DropMaster Model DMs-401, manufactured by Kyowa Interface Science Co., Ltd.) The contact angle was measured 21 seconds after a drop of pure water landed on the surface of the storage layer (A). The contact angle was calculated as the average value of the measurements at three points. The smaller the contact angle, the better the anti-fogging property.

[0123] (50℃ steam anti-fogging) Pure water was placed in a beaker and heated to 50°C. After the temperature of the pure water in the beaker reached 50° C., the laminate was placed on top of the beaker with the storage layer (A) facing downward (ie, the side facing the pure water). While maintaining this state for 10 minutes, the laminate was visually observed from above to check whether the laminate was cloudy or not. The time from the start of the above-mentioned holding until clouding of the laminate was confirmed is shown in Table 3. The longer this time, the better the anti-fogging property. In Table 3, ">10 minutes" means that no clouding of the laminate was observed within 10 minutes from the start of the above-mentioned holding.

[0124] (Anti-fog recovery times) After wiping off the liquid composition, the surface of the storage layer (A) of the laminate was washed with running pure water for 5 seconds by rubbing with a finger, and then the surface was dried by air blowing. After drying, breath was blown onto the surface for a few seconds, and the surface was visually inspected for the presence or absence of fogging. If fogging occurred, the laminate was left for up to 24 hours to determine whether the fogging caused by breath disappeared (i.e., the anti-fogging properties were restored) (the above procedures are referred to as "evaluation of breath anti-fogging properties"). In the evaluation of breath anti-fogging properties, if there was no fogging from the first breath spray stage, or if there was fogging upon the first breath spray but the anti-fogging properties were restored within 24 hours, the above-mentioned washing with pure water and drying were performed again. After drying, the breath anti-fogging property was evaluated again as described above. The above cycle was repeated, and the cycle was terminated when the anti-fogging properties of the laminate did not recover even after being left for 24 hours. The number of times of washing with water in the process until the end of the cycle was regarded as the number of times of recovery of anti-fogging property. A larger anti-fogging property recovery number means better anti-fogging property (specifically, recovery of anti-fogging property). In Table 3, "22 times or more" means that even after 22 water washes, there was no fogging from the stage of the first breath blowing, or there was fogging at the first breath blowing but the anti-fogging property was restored within 24 hours.

[0125] Example 3 The same operations as in Example 1 were carried out except for the following points. The results are shown in Table 3.

[0126] -Differences from Example 1- By using composition A2 as a composition for forming storage layer (A) instead of composition A1 as a composition for forming storage layer (A), storage layer A2 was formed as storage layer (A) instead of storage layer A1 as storage layer (A) (see Table 3). The heating conditions for the coating film of the composition for forming storage layer (A) were changed to 80°C and 20 minutes. Composition B2 was applied onto the storage layer (A) by dip coating as a composition for forming the buffer layer (B) to obtain a coating film. The dip coating was performed by using composition B2 in a PP beaker as a coating liquid, immersing the substrate in the coating liquid for 10 seconds, and then lifting it up at a speed of 300 mm per minute. The coating film of the composition for forming the buffer layer (B) formed on the storage layer (A) was heated and cured at 110°C for 60 minutes to form a buffer layer B2 as the buffer layer (B). As a result of the above, a laminate was obtained that included a substrate (an ADC lens in this Example 3), a storage layer (A) (storage layer A2 in this Example 3), and a buffer layer (B) (buffer layer B2 in this Example 3) arranged in this order. The application of the liquid composition containing an ionic surfactant and the evaluations were carried out in the same manner as in Example 1, except that the "surface of the storage layer (A)" was read as the "surface of the buffer layer (B)."

[0127] Example 5 The same operations as in Example 3 were carried out except for the following points. The results are shown in Table 3.

[0128] -Differences from Example 3- Instead of an ADC lens (φ70 mm) as the substrate, a polycarbonate (PC) plate (length 65 mm × width 65 mm × thickness 2 mm) was used as the substrate. The method of applying the composition for forming the storage layer (A) was changed from dip coating to spin coating. The spin coating was performed by first applying the composition for forming the storage layer (A-3) as a coating liquid onto the polycarbonate plate while rotating the polycarbonate plate at a rotation speed of 500 rpm for 10 seconds and gradually spreading the composition, and then rotating the polycarbonate plate at 1000 rpm for 10 seconds to spread the coating liquid. The coating film of the composition for forming the storage layer (A) was cured by irradiating the coating film with ultraviolet (UV) rays instead of heating the coating film. The UV irradiation was performed by irradiating the coating film with UV from a 1kW UV light source for 5 seconds using a UV irradiation device UB012-0BM manufactured by iGraphics. The integrated light amount was 350mJ / cm2 for UV-C. 2 , UV-A 1300mJ / cm 2 It was. The application method of the composition for forming the buffer layer (B) was changed from dip coating to spin coating. The spin coating conditions were the same as those for the composition for forming the storage layer (A). The coating film of the composition for forming the buffer layer (B) was cured by irradiating the coating film with ultraviolet (UV) rays instead of heating the coating film. The UV irradiation was performed by irradiating the coating film of the composition for forming the buffer layer (B) with UV rays from a 1kW UV light source for 10 seconds using a UV irradiation device UB012-0BM manufactured by iGraphics.

[0129] Example 7 The same operations as in Example 1 were carried out except for the following points. The results are shown in Table 3.

[0130] -Differences from Example 1- By using composition A5, which is a composition for forming storage layer (A), instead of composition A1, which is a composition for forming storage layer (A), storage layer A5 was formed as storage layer (A) instead of storage layer A1 as storage layer (A) (see Table 3).

[0131] [Examples 2, 4, 6, and 8] The same operations as in Examples 1, 3, 5, and 7 were carried out except for the following points. The results are shown in Table 3.

[0132] -Differences from Examples 1, 3, 5, and 7- Between the production of the laminate and the application of the liquid composition containing an ionic surfactant, an operation of subjecting the laminate to a water immersion treatment was added. The water immersion treatment was performed by immersing the entire laminate in water for 3 hours, taking it out, blowing off any water remaining on the surface of the laminate with an air blower, and then wiping off the water with tissue paper.

[0133] -Contact angle before and after water immersion treatment- In Examples 2, 4, 6, and 8, and Examples 9 to 11 described below, most of the nonionic surfactant (a3) ​​was released from the storage layer (A) by the water immersion treatment. In Examples 2, 4, 6, and 8, and in Examples 9 to 11 described below, the contact angle of pure water on the surface of the laminate on which the storage layer (A) was located was measured before and after the water immersion treatment using a method similar to the contact angle measurement method shown in the "Evaluation" section above. As a result, in all of the Examples, the contact angle of pure water before the water immersion treatment was 4° to 12°, but the contact angle of pure water after the water immersion treatment was 15° or more. From the above results, it was confirmed that in Examples 2, 4, 6, and 8, and Examples 9 to 11 described later, at least a portion of the nonionic surfactant (a3) ​​was released from the storage layer (A) by the above-mentioned water immersion treatment.

[0134] Example 9 The same procedure as in Example 8 was carried out except for the following points. The results are shown in Table 3.

[0135] -Differences from Example 8- By using composition A6, which is a composition for forming storage layer (A), instead of composition A5, which is a composition for forming storage layer (A), storage layer A6 was formed as storage layer (A) instead of storage layer A5 as storage layer (A) (see Table 3).

[0136] Example 10 The same operations as in Example 2 were carried out except for the following points. The results are shown in Table 3.

[0137] -Differences from Example 2- In the "application of a liquid composition containing an ionic surfactant" section, the 25% by mass aqueous solution of sodium polyoxyethylene alkyl ether sulfate (AES) (ionic surfactant) ("Hitenol 325SM" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was changed to a 25% by mass aqueous solution of sodium linear alkylbenzene sulfonate (LAS) (ionic surfactant) (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) as the liquid composition containing an ionic surfactant.

[0138] Example 11 The same procedure as in Example 1 was carried out, except that the ADC substrate was changed to a thiourethane substrate prepared as follows. The results are shown in Table 3.

[0139] -Production of thiourethane substrate- A mixed solution was prepared by adding 0.035 parts by mass of dibutyltin dichloride, 0.1 parts by mass of ZelecUN manufactured by STEPAN, 50.6 parts by mass of a mixture of 2,5-bis(isocyanatomethyl)bicyclo-[2.2.1]-heptane and 2,6-bis(isocyanatomethyl)bicyclo-[2.2.1]-heptane, 1.5 parts by mass of Viosob583 manufactured by BASF as an ultraviolet absorber, and 0.00005 parts by mass of PlastBlue8514 manufactured by Arimoto Chemical Industry Co., Ltd. The mixed solution was stirred at 25°C for 1 hour to completely dissolve the solution, and a prepared solution was obtained. Then, 25.5 parts by mass of a thiol composition containing 4-mercaptomethyl-1,8-dimercapto-3,6-dithiaoctane and 23.9 parts by mass of a thiol composition containing pentaerythritol tetrakis (3-mercaptopropionate) were added to this preparation, and the mixture was stirred at 25°C for 30 minutes to obtain a homogeneous solution (polymerizable composition for optical materials). This polymerizable composition for optical materials was degassed at 600 Pa for 1 hour, then filtered with a 1 μm PTFE filter, and the obtained filtrate (i.e., polymerizable composition for optical materials after filtration) was poured into a glass mold and heated from 25°C to 120°C over 16 hours. After heating, it was cooled to room temperature and removed from the glass mold to obtain a thiourethane resin substrate with a diameter of 81 mm.

[0140] The thickness of the storage layer (A) in each of the laminates of Examples 1 to 11 was 8.0 μm. The thickness of the buffer layer (B) in each of the laminates of Examples 3 to 6 was 3.0 μm. The thickness of each layer was measured using a thickness measuring device (ETA-ARC, manufactured by OPTOTECH).

[0141] Comparative Example 1 The same operations as in Example 1 were carried out except for the following points. The results are shown in Table 4.

[0142] -Differences from Example 1- Instead of the composition A1, which is the composition for forming the storage layer (A), SDC hard coat solution MP-1179 was used to form a hard coat layer (HC) instead of the storage layer A1 as the storage layer (A) (see Table 4). The heating conditions for the coating film were changed to 120°C and 2 hours. In this manner, a laminate including the substrate (ADC lens) and the hard coat layer (HC) was obtained. The application of the liquid composition containing an ionic surfactant and the evaluations were carried out in the same manner as in Example 1, except that the "surface of the storage layer (A)" was read as the "surface of the hard coat layer."

[0143] Comparative Example 2 The same procedure as in Comparative Example 1 was carried out except for the following points. The results are shown in Table 4.

[0144] -Differences from Comparative Example 1- An anti-reflective layer (AR) consisting of five layers was laminated by vacuum deposition on the hard coat layer in Comparative Example 1, and a fluorine-based water-repellent coating layer was further deposited by deposition, thereby obtaining a laminate including, in this order, a substrate (ADC lens), a hard coat layer (HC), an anti-reflective layer (AR) consisting of five layers, and a water-repellent coating layer (RC). The application of the liquid composition containing an ionic surfactant and the evaluations were carried out in the same manner as in Example 1, except that the "surface of the storage layer (A)" was read as the "surface of the water-repellent coating layer."

[0145] Comparative Example 3 The same operations as in Example 1 were carried out except for the following points. The results are shown in Table 4.

[0146] -Differences from Example 1- By using composition A4, a comparative composition that does not contain a nonionic surfactant, instead of composition A1, which is a composition for forming storage layer (A), storage layer A4, a comparative layer that does not contain a nonionic surfactant, was formed instead of storage layer A1 as storage layer (A) (see Table 4).

[0147] Comparative Example 4 The same operations as in Example 2 were carried out except for the following points. The results are shown in Table 4.

[0148] -Differences from Example 2- In the "application of a liquid composition containing an ionic surfactant" step, the ionic surfactant sodium polyoxyethylene alkyl ether sulfate (AES) was changed to a nonionic surfactant, Noigen LP-100 (polyoxyalkylene lauryl ether, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.).

[0149] [Table 3]

[0150] [Table 4]

[0151] As shown in Tables 3 and 4, A step of preparing a laminate including a substrate and a storage layer (A), the storage layer (A) containing a resin (a1) which is at least one of an epoxy resin and an acrylic resin, inorganic particles (a2), and a nonionic surfactant (a3); A step of applying a liquid composition containing an ionic surfactant to the surface of the laminate on the side where the storage layer (A) is disposed (i.e., the surface of the storage layer (A) when the uppermost layer is the storage layer (A), and the surface of the buffer layer (B) when the uppermost layer is the buffer layer (B)); In each of the Examples in which the method for producing an anti-fogging laminate was carried out, including the above, an anti-fogging laminate could be produced (i.e., anti-fogging properties could be imparted to the laminate) by the simple method of applying a liquid composition containing an ionic surfactant.

[0152] In contrast to each of the Examples, in Comparative Examples 1 to 3 in which a comparative layer not containing a nonionic surfactant was used instead of the storage layer (A), the antifogging properties of the laminate after coating of the liquid composition were poor. Furthermore, in Comparative Example 4, in which a liquid composition containing a nonionic surfactant was used instead of a liquid composition containing an ionic surfactant, the anti-fogging properties of the laminate after application of the liquid composition were inferior to those of the other Examples.

Claims

1. A preparation step of preparing a laminate including a substrate and a storage layer (A), the storage layer (A) containing a resin (a1) which is at least one of an epoxy resin and an acrylic resin, inorganic particles (a2), and a nonionic surfactant (a3); a coating step of coating a liquid composition containing an ionic surfactant on a surface of the laminate on which the storage layer (A) is disposed; A method for producing an anti-fogging laminate comprising the steps of:

2. The laminate includes the base material, the storage layer (A), and a buffer layer (B) in contact with the storage layer (A) in this order; The buffer layer (B) contains a resin (b1) which is at least one of an epoxy resin and an acrylic resin, and inorganic particles (b2). A method for producing the antifogging laminate according to claim 1.

3. The ionic surfactant includes at least one selected from the group consisting of fatty acid salts, alkyl ether carboxylates, alkanesulfonates, α-olefin sulfonates, α-sulfomethyl ester salts, alkylbenzenesulfonates, alkylsuccinates, alkyl sulfates, and alkyl ether sulfates. A method for producing the anti-fogging laminate according to claim 1 or 2.

4. The liquid composition does not contain an abrasive, or if it contains an abrasive, the content of the abrasive is 10 ppm by mass or less based on the total amount of the liquid composition. A method for producing the antifogging laminate according to any one of claims 1 to 3.

5. The method for producing an anti-fogging laminate according to any one of claims 1 to 4, wherein the nonionic surfactant (a3) ​​is a compound containing a polyoxyalkylene structure.

6. the preparing step includes preparing the laminate; and releasing at least a portion of the nonionic surfactant (a3) ​​from the storage layer (A) in the prepared laminate; the coating step is a step of coating the liquid composition on a surface of the laminate on which the storage layer (A) is disposed, from which at least a portion of the nonionic surfactant (a3) ​​has been released; A method for producing the anti-fogging laminate according to any one of claims 1 to 5.

7. A substrate and a storage layer (AX), The storage layer (AX) contains a resin (a1) which is at least one of an epoxy resin and an acrylic resin formed using a monomer containing two or more (meth)acryloyl groups, inorganic particles (a2), a nonionic surfactant (a3), and an ionic surfactant. Anti-fog laminate.

Citation Information

Patent Citations

  • Polyfunctional acrylic coating agent

    JP1994306324A

  • Composition for forming antifogging layer, laminate and method for producing laminate

    JP2018002865A

  • Antifogging coating composition and antifogging transparent sheet using the same

    JP2019006891A

  • Anti-fogging article and method for producing same

    WO2012077686A1

  • Film forming composition and laminate manufacture method

    WO2017217474A1